Reduction of localized abdominal fat in men through the pulsed and continuous application of combined therapy associated with the use of medium frequency excitomotor current: randomized clinical trial: REDUÇÃO DA GORDURA ABDOMINAL LOCALIZADA EM HOMENS ATRAVÉS DA APLICAÇÃO PULSADA E CONTÍNUA DE TERAPIA COMBINADA ASSOCIADA AO USO DA CORRENTE EXCITOMOTORA DE MÉDIA FREQUÊNCIA: ENSAIO CLÍNICO RANDOMIZADO (Revista Contexto & Saúde, 2022)
The purpose of the study was to evaluate and compare the effects of combined therapy in a continuous and pulsed manner associated with medium-frequency excitomotor current on the reduction of localized fat in men, and its influence on the autonomic, cardiovascular and arterial pressure systems. Containing a sample population of 18 male participants, aged between 18 and 35 years old and with an abdominal fold of up to 4 cm. Divided into two groups, the first one received the application of combined therapy in a pulsed manner and the other one in a continuous manner and both associated with medium frequency excitomotor current. Regardless of the mode of US, there were no changes in systolic and diastolic arterial pressure, in the assessment of the autonomic nervous system, significant but expected values ​​were found.
Keywords: Men, Electric Stimulation Therapy, Arterial Pressure, localized fat, Autonomic Nervous System